1997
DOI: 10.1038/42517
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional organization of a human water channel

Abstract: Aquaporins (AQP) are members of the major intrinsic protein (MIP) superfamily of integral membrane proteins and facilitate water transport in various eukaryotes and prokaryotes. The archetypal aquaporin AQP1 is a partly glycosylated water-selective channel that is widely expressed in the plasma membranes of several water-permeable epithelial and endothelial cells. Here we report the three-dimensional structure of deglycosylated, human erythrocyte AQP1, determined at 7 A resolution in the membrane plane by elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
179
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(193 citation statements)
references
References 28 publications
12
179
0
2
Order By: Relevance
“…Our data indicate that NH 3 permeability depends on the makeup of the ar͞R constriction. Comparing different classes of AQPs that pass or do not pass NH 3 , it appears that hydrophobic niches at the entry site are needed to permit NH 3 passage. Indeed, NH 3 permeability correlated well with the lipophilicity of the ar͞R constriction present in the different AQP1 mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data indicate that NH 3 permeability depends on the makeup of the ar͞R constriction. Comparing different classes of AQPs that pass or do not pass NH 3 , it appears that hydrophobic niches at the entry site are needed to permit NH 3 passage. Indeed, NH 3 permeability correlated well with the lipophilicity of the ar͞R constriction present in the different AQP1 mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4B). However, because AQPs lack the ability to abstract a proton from an NH 4 ϩ ion, ammonia passage relies on the pH-dependent concentration of uncharged NH 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent experiments using radiolabeled inhibitors of water diffusion in red blood cells (RBC), followed by SDS-PAGE and autoradiography, reveal radiolabeled proteins migrating at the band 4.5 region, suggesting the radiolabeled bands to be possible water channels (Benga et al, 1986a,b). In the past decade, the water channel Aquaporin-1 (AQP-1), has been purified, cloned, and its crystal structure determined (Cheng et al, 1997;Denker et al, 1988;Preston and Agre, 1991;Preston et al 1992;Walz et al, 1997). A 2.2 angstrom resolution structure of the bovine AQP-1 has recently been obtained by X-ray crystallography (Sui et al, 2001), revealing the site of water molecules in a frozen state.…”
Section: Introductionmentioning
confidence: 99%
“…Moderate resolution projection and low resolution 3-D maps of AQP1 derived from electron crystallographic studies provided the first structure based evidence for a general architecture consisting of six helices surrounding two putative helical structures within the membrane bilayer [8][9][10][11] . Models of AQP1 derived from electron crystallographic structural studies at about 4 Å resolution have recently been reported and independently confirmed the presence of two non-membrane spanning helices [12][13][14] .…”
mentioning
confidence: 99%